Mandibular Coronoid Process Displacement: Signs, Causes, Treatment - Hazewinkel, H. A. W.; Koole, R.; Voorhout, G. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Open-mout h locking due to lateral impingement of the mandibular coronoid process, lateral to the zygomatic arch, is described in five dogs and one cat. In order to elucidate the underlying cause of this abnormality, radiographs of temporomandibular joints of forty dogs, as well as the case history of a human patient, are compared. Three possible aetiologies are given, namely, flattening of the zygomatic arch, aberrant architecture of the condylar aspects, or contracture of the pterygoid muscle. An effective surgical treatment to prevent recur-rence of coronoid impingement was achieved by ostectomy of the locking part of the coronoid process.Unilateral protrusion of the mandible is described as a veterinary and comparative abnormality in five dogs, a cat and a woman. For the impingement of the coronoid process lateral of the zygomatic arch causing open-mouth locking in the animals, three aetiologies and an effective ostectomy of the coronoid process are given.
Keywords: Mandibular dislocation; dog; cat; comparative